Leadership, values and authority: what shapes a manager’s work ethos and plays a key role in authority creation? - Agnieszka Postuła (Central European Management Journal)
Purpose – The article aims to identify and classify competencies and values considered essential or even necessary in the daily work of active managers and leaders. Design/methodology/approach – This article is based on the results of comprehensive ethnographic research. I acquired the research material through open interviews (26 items), which facilitated immersion into the social reality of individual groups of respondents. Findings – A manager who consistently adheres to their values builds lasting authority. A manager who is guided by values also has a greater influence on decision-making and team relationships. A manager who adheres to values can contribute to improving organizational culture and thus increase employee engagement and achieve better organizational results. Research limitations/implications – Findings from qualitative studies are context-specific and may not be easily generalizable to other settings or populations. Practical implications – Organizations need to recognize the centrality of values in building managerial authority. By strategically aligning values, promoting consistency and fostering a culture of trust, organizations can enhance managerial effectiveness, team relationships and overall organizational performance. Social implications – Managers’ values play a crucial role in shaping workplace dynamics and can extend their influence to broader societal contexts. A values-driven approach has the potential to create positive social impacts and thus contribute to ethical business practices, trustful relationships and overall societal well-being. Originality/value – The findings are original and valuable because they holistically explore the connection between managerial values and authority and identify key factors that contribute to lasting and impactful leadership in organizations and society.